2018
DOI: 10.1007/s00280-018-3695-4
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, single-blind, single-dose study to assess the pharmacokinetic equivalence of the biosimilar ABP 215 and bevacizumab in healthy Japanese male subjects

Abstract: PurposeAnalytic, pharmacokinetic (PK), and clinical similarity between the biosimilar ABP 215 and bevacizumab has previously been demonstrated in global studies. Here we present a phase 1 study in healthy adult Japanese men.MethodsThis study was a randomized, single-blind, single-dose, parallel-group study comparing PK parameters of ABP 215 versus EU-authorized bevacizumab in healthy Japanese men. Primary endpoints were maximum observed serum concentration (Cmax) and area under the serum concentration—time cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 4 publications
5
15
0
Order By: Relevance
“…The treatment group ratios of LS geometric means for the three primary PK parameters were fully contained within the bioequivalence limits of 80–125%. These results were consistent with other similar studies in Caucasian, Japanese, Korean, and Chinese healthy volunteers ( Table 5 ) (Knight et al, 2016; Hettema et al, 2017; Markus et al, 2017; Tajima et al, 2017; Hanes et al, 2018; Zhang et al, 2018; Cho et al, 2019; Wu et al, 2019; Zhang et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The treatment group ratios of LS geometric means for the three primary PK parameters were fully contained within the bioequivalence limits of 80–125%. These results were consistent with other similar studies in Caucasian, Japanese, Korean, and Chinese healthy volunteers ( Table 5 ) (Knight et al, 2016; Hettema et al, 2017; Markus et al, 2017; Tajima et al, 2017; Hanes et al, 2018; Zhang et al, 2018; Cho et al, 2019; Wu et al, 2019; Zhang et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…TEAEs considered related to the study drug in this study were reported for 19 (38.8%) subjects in the TAB008 group and 19 (38.0%) subjects in the Avastin ® group. AE seemed to vary widely between these studies (Knight et al, 2016; Hettema et al, 2017; Markus et al, 2017; Tajima et al, 2017; Hanes et al, 2018; Zhang et al, 2018; Cho et al, 2019; Wu et al, 2019; Zhang et al, 2019), but there was no significant correlation with the dose. The %AE with 1 mg/kg ranged across studies from 33.3% to 55.0% for biosimilars and 32.3% to 48.8% for Avastin ® (EU-sourced).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Moreover, results confirm that bevacizumab-EU and bevacizumab-US are bioequivalent to each other, consistent with results from other phase I studies of bevacizumab biosimilars [16,17]. The PK results of this study are consistent with those of other phase I PK studies of (proposed) bevacizumab biosimilars which also demonstrated equivalence to the reference product [16][17][18][19][20][21][22][23][24][25][26]. However, direct comparisons of absolute PK parameters values between studies are generally not appropriate due to differences between the doses used (1 mg/kg, 3 mg/kg or 5 mg/kg), sample collection, and assessment methods [16][17][18][19][20][21][22][23][24][25][26].…”
Section: Discussionsupporting
confidence: 89%
“…Although mCRC is one of the indications for which bevacizumab is most commonly prescribed in clinical practice, 54,55 it is a less sensitive patient population for comparing bevacizumab biosimilars with bevacizumab RP. In pivotal phase III trials in AUC inf and C max were similar across the 3 arms GMRs between treatment arms for C max and AUC inf , respectively, were 0.98 and 0.99 for ABP 215 vs. bevacizumab (US); 1.03 and 0.96 for ABP 215 vs. bevacizumab (EU); and 1.05 and 0.97 for bevacizumab (US) vs. bevacizumab (EU) 90% CIs for the GMRs of AUC inf and C max were within the prespecified bioequivalence margin ABP 215 26 Randomized, open-label, single-dose study C max , AUC last , and AUC inf were similar across the three arms GMRs between treatment arms for C max , AUC last , and AUC inf , respectively, were 104%, 100%, and 99% for PF-06439535 vs. bevacizumab (EU); 110%, 104%, and 103% for PF-06439535 vs. bevacizumab (US); and 105%, 105%, and 105% for bevacizumab (EU) vs. bevacizumab (US) 90% CIs for the GMRs of C max , AUC last , and AUC inf were within the prespecified bioequivalence margin SB8 28 Randomized, open-label, single-dose study treatment-naive mCRC, adding bevacizumab RP to chemotherapy significantly improved PFS, but the impact on ORR was small and varied between studies. 56,57 Furthermore, ORR may not reliably predict PFS and OS in this patient population.…”
Section: Demonstrating Biosimilaritymentioning
confidence: 94%